Socio-structural and psychological factors behind car use: Comparing Northern and Eastern Europe. (January 2019) - Orru, Kati; Poom, Age; Nordlund, Annika
Highlights: Travel intention is activated by social traditions, and infrastructures. Values have a more pronounced effect on the trips of Estonians. In stratified societies, higher social status predicts higher frequency of car trips. Spatial stratification significantly shapes car travel in Estonia, but not in Sweden. Abstract: This study explores cross-cultural differences in car travel behaviour in a northern and an eastern European country, namely Sweden and Estonia. We assess the role of country-specific socio-structural circumstances, and the influence of individual motivations, including social values, perceived seriousness of environmental problems associated with car use, and car use reduction intentions, in shaping the frequency of car use for different purposes. The results show that compared to Swedish people, people in Estonia are more dependent on cars in their everyday travel. Our study shows that higher social position is associated with higher frequency of car trips in more stratified Estonian society, but not necessarily where socio-economic differences are less pronounced, as in Sweden. Regarding the relative significance of values and intentions next to socio-economic determinants, values and intentions have a greater explanatory power of car use frequency in Estonia, compared to Sweden. That values and preferences play a smaller role in car travel frequency in the socio-economically more secure Sweden, indicates that car travel is a basic habit, which is not easily discernible through individual values and attitudes in more affluent societies. Differences in car travel frequencies between the respondents from different settlement types in Estonian but no differences between settlement types in Sweden, shows that a country's broader approach to managing the economic and social viability of its regions, may shape car travel needs and opportunities. The results of this study may have implications in terms of ways of curbing emissions from transportation in different parts of Europe.